A Quasi-Experimental Study of a Movement and Preliteracy Program for 3- and 4-Year-Old Children - Chloe Bedard; Emily Bremer; Wenonah Campbell; John Cairney; John Cairney; John Cairney (Frontiers Media S.A., 2017)
ObjectiveApproximately 28% of children are not ready for kindergarten, 91% are inactive according to current guidelines, and 21% are overweight/obese. Early intervention to strengthen movement and preliteracy skills may help to curb the concerning rates of poor school readiness, inactivity, obesity, and subsequently positively impact health across the lifespan. The objective of this pilot study was to evaluate the effectiveness of a motor and preliteracy skill program for a community sample of 3- to 4-year-old children.MethodsA quasi-experimental study design was used. The program was run for 1 h/week for 10 weeks and consisted of movement skill instruction, free play, and an interactive reading circle with care-giver involvement throughout each session. Movement and preliteracy skills were assessed in all children pre- and post-intervention using the Peabody Developmental Motor Scales-2nd edition, the Preschool Word and Print Awareness tool, and the Phonological Awareness Literacy Screening tool.ResultsNineteen families (experimental group, n = 8; control group, n = 11) were recruited (mean age = 3 years, 8 m; 47% male). There was a significant effect of group on gross motor raw scores overall [F(1, 16) = 4.67, p < 0.05; ωp2=0.16] and print-concept knowledge [F(1, 16) = 11.9, p < 0.05; ωp2=0.38].ConclusionThis study was one of the first to examine the impact of a community-based movement skill and preliteracy program with care-giver involvement in preschool children. Future research should continue to explore the effects of the program with larger and more diverse samples on multiple health and developmental outcomes.Clinical Trial RegistrationPlay and Preliteracy among Young Children (PLAY) NCT02432443.